Preparation and characterization of a red luminescent composite composed of an EVA copolymer and a Y3BO6:Eu3+ phosphor - Chapel, Anthony; Boonsin, Rachod; Chadeyron, Geneviève; Boyer, Damien; Bousquet, Angélique; Mahiou, Rachid; Henrique Cassinelli, Wellington [UNESP]; Santilli, Celso Valentim [UNESP]; Therias, Sandrine (Royal Society of Chemistry (RSC), 2017)
This work describes the preparation of red luminescent composites based on an ethylene/vinyl acetate (EVA) copolymer filled with a Y3BO6:Eu3+ phosphor powder. Luminescent powders were synthesized using a method derived from the Pechini synthesis method. The powders were then homogeneously dispersed in an EVA copolymer solution to achieve luminescent composite films. The structural, morphological and optical properties of the red luminescent composite films were investigated. The dispersion of phosphor particles in an EVA copolymer did not globally modify their optical features. However, the presence of an Eu3+-O2- charge transfer excitation band was observed and attributed to the effect of the refractive index of the EVA copolymer. Finally, the optical studies of these films evidenced their compatibility with commercial ultra-violet light emitting diodes (LEDs).